Oszacowanie parametrów liniowych okrętu w pewnym zbiorze obciążeń - WIĘCKOWSKI, Jan (Engineering Transactions, 1966)
Estimation of the linear parameters of a ship in some a set loadsThe object of the considerations is the problem of integral extrema of the functional (2.1) in the set (2.3) of continuous functions having sectionally continuous derivatives. After reducing the problem to the equivalent extremum problem of the linear functional (2.12) in the set of functions (2.13) sectionally continuous and bounded, the extremal function and the values of the extrema are obtained.In Sec. 3 is considered a particular case of extremum of the functional (2.1) in the set (3.1) having, in the case of extremal function nonnegative in the entire interval, a physical interpretation of (in the form of) the extremal distribution of a granular shipload in the hold of a ship.If the extremal function in the set (3.1) is not nonnegative in the entire interval, estimates from above and from below are obtained for the integral extrema of the functional (2.1), in the set of nonnegative functions belonging to the set (3.1).In conclusion, the problem of technical interpretation described in another paper [8] is discussed and solved on the basis of general solutions and estimations obtained in the present paper. Directions of further research are suggested.